2021
DOI: 10.1088/1361-6560/abd956
|View full text |Cite
|
Sign up to set email alerts
|

GroupRegNet: a groupwise one-shot deep learning-based 4D image registration method

Abstract: Accurate deformable four-dimensional (4D) (three-dimensional in space and time) medical images registration is essential in a variety of medical applications. Deep learning-based methods have recently gained popularity in this area for the significantly lower inference time. However, they suffer from drawbacks of non-optimal accuracy and the requirement of a large amount of training data. A new method named GroupRegNet is proposed to address both limitations. The deformation fields to warp all images in the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…There are in general three different types of groupwise registration: sum-of-pairs approach that attempts to reduce the registration loss among all image pairs; reference-based approach that requires the designation of one image as reference; implicit template approach that implicitly determines the template image during registration, and can avoid the bias caused by selecting one particular image as reference while being more computationally efficient than the sum-of-pairs method ( 41 ). Deep learning groupwise registration has been adopted in several recent studies ( 36 , 37 , 42 ) and has demonstrated superior performance over pairwise registration. For example, Zhang et al propose an one-shot learning groupwise registration network to register respiratory motion-resolved 3D CT images ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are in general three different types of groupwise registration: sum-of-pairs approach that attempts to reduce the registration loss among all image pairs; reference-based approach that requires the designation of one image as reference; implicit template approach that implicitly determines the template image during registration, and can avoid the bias caused by selecting one particular image as reference while being more computationally efficient than the sum-of-pairs method ( 41 ). Deep learning groupwise registration has been adopted in several recent studies ( 36 , 37 , 42 ) and has demonstrated superior performance over pairwise registration. For example, Zhang et al propose an one-shot learning groupwise registration network to register respiratory motion-resolved 3D CT images ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning groupwise registration has been adopted in several recent studies ( 36 , 37 , 42 ) and has demonstrated superior performance over pairwise registration. For example, Zhang et al propose an one-shot learning groupwise registration network to register respiratory motion-resolved 3D CT images ( 36 ). Martín-González et al ( 42 ) develop a deep learning framework to achieve groupwise registration of 2D dynamic sequence, in which the implicit template deep learning groupwise registration approach is adopted to estimate the nonrigid motion across the dynamic sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have proposed to use the convolutional neural network as a feature extractor for registering multiple 3DCT images. 20,21 In essence, their one-shot methods are traditional iterative optimization methods since their networks still need to be optimized when registering new images. The way they use the network is equivalent to taking the input as the training sample as well as the test sample instead of learning from other samples, which is prone to overfitting and lacks stability.…”
Section: Introductionmentioning
confidence: 99%
“…Image registration is the process of aligning the images together that are misaligned due to organ or patient movement. We have studied a few learning-based denoising and registration methods where individuals are trying to solve these two problems independently [3][4][5][6][7][8]. But it is essential to jointly look at these two issues together instead of dealing with each one separately.…”
Section: Introductionmentioning
confidence: 99%